2018
DOI: 10.1002/hep4.1135
|View full text |Cite
|
Sign up to set email alerts
|

Acute decompensation boosts hepatic collagen type III deposition and deteriorates experimental and human cirrhosis

Abstract: Patients with end‐stage liver disease develop acute decompensation (AD) episodes, which become more frequent and might develop into acute‐on‐chronic liver failure (ACLF). However, it remains unknown how AD induces acceleration of liver disease. We hypothesized that remodeling of collagen type III plays a role in the acceleration of liver cirrhosis after AD and analyzed its formation (Pro‐C3) and degradation (matrix metalloproteinase‐degraded type III collagen [C3M]) markers in animal models and human disease. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 33 publications
3
50
0
2
Order By: Relevance
“…Importantly, ECM is highly dynamic as shown in HIV patients receiving antiretroviral treatment, which led to attenuation of remodelling of collagen type IV and elastin, but not collagen type III and biglycan . Recently, collagen type III deposition was shown to be boosted in AD and ACLF . The present study suggests that the levels of collagen type IV remodelling markers do not accumulate with impaired renal function.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…Importantly, ECM is highly dynamic as shown in HIV patients receiving antiretroviral treatment, which led to attenuation of remodelling of collagen type IV and elastin, but not collagen type III and biglycan . Recently, collagen type III deposition was shown to be boosted in AD and ACLF . The present study suggests that the levels of collagen type IV remodelling markers do not accumulate with impaired renal function.…”
Section: Discussionsupporting
confidence: 55%
“…AD of cirrhosis might progress to multiple organ failure, defining acute‐on‐chronic liver failure (ACLF) with poor survival . Interestingly, AD might boost the net deposition of collagen type III, a major component of the interstitial matrix, suggesting a new role of ECM in decompensated cirrhosis …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In both studies, significant changes in PRO‐C3 level from baseline were observed as a result of therapy . There are limited studies regarding the predictive value of PRO‐C3; however, studies have shown that PRO‐C3 has the ability to predict decompensation and mortality in patients with liver disease, and to predict transplant‐free survival in patients with PSC . However, further investigation regarding the predictive and prognostic value of PRO‐C3 is required, as well as its relationship to clinical outcomes.…”
Section: The Clinical Utility Of Pro‐c3mentioning
confidence: 99%